2012
DOI: 10.1124/dmd.112.048819
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hybrid Approach Based on Empirical and Physiological Concept for Predicting Pharmacokinetics in Humans—Usefulness of Exponent on Prospective Evaluation of Predictability

Abstract: We developed a hybrid method for predicting plasma concentration-time curves in humans by integrating species differences in in vitro intrinsic clearance (CL int ) into the Dedrick approach based on the allometry concept. With prediction of clearance (CL) by allometric scaling, taking in vitro CL int into consideration improved the accuracy and reduced the average fold error from 2.72 to 1.99. With the hybrid approach of applying the same concept to the Dedrick approach, the predictability of plasma concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In the comparative study that we had previously conducted, it was revealed that the prediction accuracy of V ss estimated from plasma concentration–time curves predicted with the PBPK model was lower than that with the hybrid Dedrick approach (AFE; 1.95 vs. 1.54). The PBPK model utilizes TC‐based equations in which plasma protein binding, clog P , and p K a are substituted to estimate the K p value of each tissue.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In the comparative study that we had previously conducted, it was revealed that the prediction accuracy of V ss estimated from plasma concentration–time curves predicted with the PBPK model was lower than that with the hybrid Dedrick approach (AFE; 1.95 vs. 1.54). The PBPK model utilizes TC‐based equations in which plasma protein binding, clog P , and p K a are substituted to estimate the K p value of each tissue.…”
Section: Discussionmentioning
confidence: 92%
“…The clog P , pH‐dependent measure of lipophilicity (clog D ), and p K a were calculated using CLOGP, version 4.82 (Daylight Chemical Information Systems Inc., Laguna, Niguel, CA, USA) and Pallas, version 4.4.1 (CompuDrug Inc., Sedona, AZ, USA). The compounds were divided into acidic, basic, and neutral classes based on the difference between the clog D values at pH 6.5 and 7.4, according to the previous report …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PBPK model and interspecies allometric scaling are two common methodologies for the prediction (Poulin et al, 2011; Vuppugalla et al, 2011). Although interspecies allometric scaling has been frequently used (Iavarone et al, 1999; Kang et al, 2009; Sayama et al, 2013), PBPK model, considered as a mechanism-based methodology, shows several advantages (Pang and Durk, 2010; Poulin et al, 2011; Jones and Rowland-Yeo, 2013). Interspecies allometric scaling highly depends on animal study, which should be performed with at least three animal species.…”
Section: Introductionmentioning
confidence: 99%